2021
DOI: 10.3390/pathogens10010038
|View full text |Cite
|
Sign up to set email alerts
|

Limits and Opportunities of SARS-CoV-2 Antigen Rapid Tests: An Experienced-Based Perspective

Abstract: Background: Due to the steadily rising case numbers of SARS-CoV-2 infections worldwide, there is an increasing need for reliable rapid diagnostic devices in addition to existing gold standard PCR methods. Actually, public attention is focused on antigen assays including lateral flow tests (LFTs) as a diagnostic alternative. Therefore, different LFTs were analyzed regarding their performance in a clinical setting. Material and Methods: A pilot sample panel of 13 bronchoalveolar fluids (BALFs) and 60 throat wash… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 11 publications
8
72
0
1
Order By: Relevance
“…The study Ag-RDT fulfilled the current World Health Organization (WHO)'s recommendations for a screening Ag-RTD stating that, at minimum, Ag-RDTs would need to correctly identify significantly more cases than they would miss (sensitivity !80%) and would have very high specificity (!97-100%) (World Health Organization, 2020a). Furthermore, analytical performances of comparable order as those of our study Ag-RDT were previously reported for some Ag-RDTs in lateral flow immunoassay format (Cerutti et al, 2020;Chaimayo et al, 2020;Diao et al, 2021;Favresse et al, 2021;Linares et al, 2020;Schildgen et al, 2021;Toptan et al, 2020;Weitzel et al, 2020), while several studies have reported much lower sensitivity levels contrasting with always high specificity (Albert et al, 2020;Dinnes et al, 2020;Scohy et al, 2020;Yamayoshi et al, 2020;Osterman et al, 2021;Torres et al, 2021).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The study Ag-RDT fulfilled the current World Health Organization (WHO)'s recommendations for a screening Ag-RTD stating that, at minimum, Ag-RDTs would need to correctly identify significantly more cases than they would miss (sensitivity !80%) and would have very high specificity (!97-100%) (World Health Organization, 2020a). Furthermore, analytical performances of comparable order as those of our study Ag-RDT were previously reported for some Ag-RDTs in lateral flow immunoassay format (Cerutti et al, 2020;Chaimayo et al, 2020;Diao et al, 2021;Favresse et al, 2021;Linares et al, 2020;Schildgen et al, 2021;Toptan et al, 2020;Weitzel et al, 2020), while several studies have reported much lower sensitivity levels contrasting with always high specificity (Albert et al, 2020;Dinnes et al, 2020;Scohy et al, 2020;Yamayoshi et al, 2020;Osterman et al, 2021;Torres et al, 2021).…”
Section: Discussionsupporting
confidence: 82%
“…Around 150 Ag-RDTs for SARS-CoV-2 infection are now commercially available or in development (FindDx, 2021). However, there is significant variability reported with respect to their diagnostic performances and a lack of external validation for many of the available tests, which still require clinical validation (Dinnes et al, 2020;Mattiuzzi et al, 2020;Favresse et al, 2021;Fitzpatrick et al, 2021;Schildgen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Some papers reported that the sensitivity was not so high for these antigen tests even though they were a little better than the tests that were not listed on EUL [49][50][51].…”
Section: Antigen Tests For Covid-19mentioning
confidence: 99%
“…To date, most of these validations were carried out in symptomatic individuals or using previously collected samples (Cerutti et al, 2020;Kruttgen et al, 2021;Porte et al, 2020;Weitzel et al, 2020;Yamayoshi et al, 2020). In contrast, onsite test validation studies in asymptomatic individuals, to support the use of RAT in mass testing and epidemiological surveillance, are limited (Jakobsen et al, 2021;Mina et al, 2020;Pollock et al, 2021;Schildgen et al, 2021;Toptan et al, 2021). This study performed a mass comparison of RAT and real-time RT-PCR test in asymptomatic individuals from a Chilean region.…”
Section: Introductionmentioning
confidence: 99%